The concept of macroeconomic vulnerability. A review of the literature - Portillo-Riascos, Luis Hernando (Sociedad y Economía, 2020)
The objective of this study is to review the meaning and scope of the concept of macroeconomic vulnerability (MV), emphasizing the situation faced by developing economies. For this purpose, a literature review of the most relevant publications on this topic was carried out. As a result of this study, three approaches were identified that address the VM study: (a) the structural one; (b) the one that associates the VM with the occurrence of crisis episodes; and (c) the one that argues that the VM is related to real macroeconomic instability. Beyond the contrasts that were found between the different theoretical positions, it is concluded that the VM is a phenomenon deeply rooted in the Latin American economies, whose consequences have worsened as a result of the deepening of trade and financial integration that has taken place in recent decades.